A PANEL DATA PERSPECTIVE ON TRIPLE BOTTOM LINE IMPLEMENTA-TION AND FINANCIAL PERFORMANCE OF INDONESIA'S STATE-OWNED BANKS (2020-2024) - Priska Basariana Panggabean (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study investigates how adopting a Triple Bottom Line (TBL) framework influences the financial performance of Indonesian state-owned banks. Drawing on Stakeholder and Signaling Theories, the research treats the Planet and People dimensions of TBL as indicators of management quality and organizational resilience. Using a quantitative panel data approach covering four major state-owned banks — Bank Mandiri, BNI, BRI, and BTN — across 2020 to 2024, the study generates 20 observations. The Planet dimension is measured through the Green Financing Ratio (GFR), while Social Disclosure Intensity (SDI) derived from a 40-item GRI 400-series checklist, captures the People dimension. Return on Assets (ROA) is used as the primary performance measure, with bank size and Non-Performing Loans (NPL) included as control variables. Analysis was conducted using Linear Mixed Models in IBM SPSS 29, with an AR(1) covariance structure to address serial correlation within banks. The results reveal that GFR has a modest positive but statistically insignificant relationship with ROA, while SDI shows virtually no effect, resulting in both hypotheses being rejected. Importantly, neither TBL variable harmed profitability, countering the notion that sustainability practices come at a financial cost. The high autocorrelation detected suggests that bank-specific historical performance is the dominant driver of ROA, potentially masking any short-term effects of TBL. Overall, the findings position TBL adoption as financially neutral at worst and modestly beneficial at best, with fuller profitability gains likely emerging over longer periods — offering practical guidance for sustainable resource planning in line with OJK's Sustainable Finance Roadmap Phase II.